Complete plastome sequence of Antirhea chinensis (Champ. ex Benth.) Forbes et Hemst: An endemic species in South China. Issue 1 (2nd January 2019) - Fan, Wei-Wei; Wang, Jian-Hua; Zhao, Kun-Kun; Wang, Hong-Xin; Zhu, Zhi-Xin; Wang, Hua-Feng
Abstract: Antirhea chinensis is a plant of the family Rubiaceae. So far, there is no study on the genome of A. chinensis. Here we report and characterize the complete plastid genome sequence of A. chinensis in an effort to provide genomic resources useful for promoting its conservation. The complete plastome is 155, 616 bp in length and contains the typical structure and gene content of angiosperm plastome, including two inverted repeat regions of 25, 690 bp, a large single copy region of 86, 252 bp and a small single copy region of 17, 984 bp. The plastome contains 114 genes, consisting of 80 unique protein-coding genes, 30 unique tRNA genes, and 4 unique rRNA genes. The overall A/T content in the plastome of A. chinensis is 62.40%. The complete plastome sequence of A. chinensis will provide a useful resource for the conservation genetics of this species as well as for the phylogenetic studies for Rubiaceae.